2003
DOI: 10.1039/b305802f
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of chromia/alumina catalyst monitored by DRIFTS-mass spectrometry and TPR-Raman spectroscopy

Abstract: The reduction of alumina-supported chromia with 13 wt.% chromium was investigated by X-ray photoelectron and X-ray absorption spectroscopies, in situ temperature-programmed Raman spectroscopy and in situ temperature-programmed diffuse reflectance infrared Fourier transform spectroscopy combined with mass spectrometry. For comparison, unsupported chromia was also studied. The oxidised chromia/ alumina contained Cr 3+ and Cr 6+ , whereas after reduction by carbon monoxide or hydrogen mainly Cr 3+ was detected, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…After reaction, the amount of isolated tetrahedral Cr VI species decreased dramatically, which may be due to the coke Therefore, it seems that coke formation is more favored on oligomeric chromium species than on polymeric ones. In addition, it can be seen that a structural rearrangement of polymeric chromium species on Cr/K/Al 2 O 3 to oligomeric species Page 17 of 40 A c c e p t e d M a n u s c r i p t may take place during reaction process [19,20,32]. ***FIGURE 10***…”
Section: Page 14 Of 40mentioning
confidence: 98%
“…After reaction, the amount of isolated tetrahedral Cr VI species decreased dramatically, which may be due to the coke Therefore, it seems that coke formation is more favored on oligomeric chromium species than on polymeric ones. In addition, it can be seen that a structural rearrangement of polymeric chromium species on Cr/K/Al 2 O 3 to oligomeric species Page 17 of 40 A c c e p t e d M a n u s c r i p t may take place during reaction process [19,20,32]. ***FIGURE 10***…”
Section: Page 14 Of 40mentioning
confidence: 98%
“…Infrared (IR) spectroscopy has been one of the most important means of studying adsorbates on supported catalysts [2,[24][25][26][27]. The development of in situ IR cells has permitted investigation of IR-observable adsorbates during reaction [28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…These results revealed the formation of polymolybdate species other than the isolated Td-Mo. Airaksimen et al [23] reported that the appearance of a band at 900 cm −1 is assigned to the vibration of Mo-O-Cr in molybdenum dichromate and that at 2000 cm −1 , it is assigned to chromate vibration. The band at 850 cm −1 is assigned to Cr-O-Cr vibration.…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 97%